ОБ ИСТОРИИ ЧЕРЕДОВАНИЯ ГЛАСНЫХ іі/И В КОРНЕВОМ СЛОГЕ В РУССКОМ ЯЗЫКЕ - ВЯЗИКОВА, ЛАРИСА (Studia Rossica Posnaniensia, 2006)
In present-day Russian we can very often observe the alteration of the root vowels in grammatical forms of the words and derivatives. This phenomenon was much more widely spread in the earlier periods of the Russian language. This vowel alteration wasn’t caused by any phonetic changes in Old Russian being a spontaneous process inherited from the pre-written period of language development. Thus the alteration іУн frequently found in medieval texts (cp. съм'кр/съмир, тФш/тиш) goes back to Indo-European *e/*i and plays the sense differentiating role. These words had retained the phonetic differences till the decay of the reduced vowels. The root vowels began to get mixed in the 13-th century. Since the 15-th century the homonyms began to be differentiated in spelling.